VOCATIONAL EDUCATION SYSTEMS IN GERMANY AND TURKEY: COMPARATIVE ANALYSIS - Pleshakova, Anastassia (Revista Inclusiones, 2021)
The purpose of the article is to compare vocational education systems in Germany and Turkey (using the dual system as an example) in order to identify the possibilities of transferring ideas and practices of the dual education system. Comparative analysis is the leading research method, which uses the context, transfer and forecasting methodology. Description and comparison of the context main elements allow to determine the possibilities and conditions of the dual education system transfer. The findings provide an opportunity to identify transfer risks and predict the consequences of borrowing. The research results significance consists in context, transfer and forecasting substantiating as the comparative analysis elements and applying this methodology to the processes of professional education.